Culture and Faith Encounter Spaces: An Intercultural Approach to Sasi Worship in Formulating Contextual and Responsive Christian Religious Strategies - Mike Makahenggang (PT FORMOSA CENDEKIA GLOBAL, 2026)
This article discusses culture and faith through an intercultural approach in the approach of Christian Religious Education (PAK) and places the traditional culture of Sasi worship in Halmahera as the main case study. This research uses a reflective qualitative approach with hermeneutic, phenomenological and cultural philosophical analyses to interpret the meaning of Sasi worship as a cultural practice but which has also undergone integration with the Christian faith. The results of the study will try to show that Sasi worship is not only a celebration of buaday with a customary-ecological mechanism, but also a theological and pedagogical space in representing ecological spirituality, responsibility ethics, and contextual and transformative faith education. From the perspective of PAK, this tradition serves as a learning medium for grounded faith, teaching the value of creation ministry, social solidarity and life balance.